Can surgical treatment for benign prostatic hyperplasia improve sexual function? A systematic review. (4th December 2020) - Soans, Julian; Vazirian-Zadeh, Mahmood; Kum, Francesca; Dhariwal, Randeep; Breish, Mohamed Omran; Singh, Sohail; Mahmalji, Wasim; Katmawi-Sabbagh, Samer
Abstract: Introduction: Erectile dysfunction is an established, well known risk of any operative management of benign prostatic hyperplasia (BPH). However, there are some cases reported in which surgical treatment has paradoxically improved erectile function. Here, we present a systematic review of the literature pertaining to the effect of surgery on sexual function, focusing on reports of improvement in erectile function following surgery. Materials and methods: We searched PUBMED, EMBASE, Web of Knowledge, and SCOPUS databases for the following keywords: (("sexual function" OR "erectile function") AND "improvement" AND "benign prostatic hyperplasia" AND "surgery"). Results: Sixteen studies (total n = 2087) were reviewed which reported a significant improvement in any aspect of erectile function. Ten of these studies had a follow-up period of 12 months or more while five had a follow up less than 12 months. Various surgical methods were included in the 16 studies; however, five reported TURP outcomes specifically. Eleven studies reported outcomes using the International Index of Erectile Function (IIEF). Overall, a further 87 studies showed no significant change and 8 studies showed a significant reduction. Conclusions: The majority of studies report no change in erectile function following surgical intervention for BPH. There seems to be no obvious correlating factor between the studies reporting an improvement in erectile function. Further research is needed to guide us in how to consent our patients for erectile function outcomes for BPH surgery.